Importance of hair trace metal analysis after pectus bar implantation - Akkus, Murat; Seyrek, Yunus; Binnaz Yoruc Hazar, Afife; Sahin, Fikrettin (Annals of Medical Research, 2021)
Aim: This study aimed to determine if there was a significant increase in scalp hair levels of trace metals in children with implanted pectus bars and investigate previously unreported hair metal levels after minimally invasive repair of pectus excavatum (MIRPE). Materials and Methods: Between November 2013 and December 2019, we prospectively collected scalp hair samples from patients before MIRPE and prior to pectus bar explantation (1 day before bar removal) to evaluate trace metal levels following the implantation of metal bars. Two study groups were involved: a group of consecutive patients who underwent pectus bar removal 2–5 years after MIRPE (study group, n = 97), and a group including the same patients (control group, n = 97) prior to MIRPE.Results: The mean patient age was 13.3 ± 2.7 years (range, 11–19 years) preoperative and 16.4 ± 2.3 years (range 14–23 years) postoperative; 64% of the patients were male (n = 62). Statistically significant increases in all studied trace metal levels (chrome, iron, nickel, and molybdenum) were identified in the intergroup comparison of hair trace metal analysis.Conclusion: The results of this prospective study show that hair is a good biological marker for the monitoring and study of trace metals released from pectus bars. This simple assessment may be useful for the screening of trace metal increase due to the pectus bar. When metal allergy is suspected during follow-up after MIRPE, the availability of preoperatively collected hair samples will be quite beneficial.
Keywords: Hair trace metals; metal allergy; stainless steel pectus bar